Leaving Cheyenne (Southwest landmark, no. 3,, 1986)
Leaving CheyenneLonesome Dove

The cowboy life in short stories and poems (J. McArthur, J'Wayne McArthur, The Author, 1986)
Description Not Provided
Dreams do come true --, Boy's love for his horse --, To be a cowboy --, Roping the big ones and the little ones --, Chester, the dog-tailed horse --, Wonderful winter time --, One day I'll get even --, Outsider in Wyoming --, Butch Cassidy in Pinedale --, Those colored eggs --, Mail time on the ranch --, Ranch hand or cowboy --, Trip back into memories --, Dogs, rabbits and horses don't mix --, Ever try to load a snaky horse? --, Ghost of a deer --, My friend Leo --, If you drink don't buy --, Trying to do the job alone --, Mowing hay the old way --, Car dealer's horse --, Deep conversation can bury you --, Traveling salesman --, Trying to get rid of my kids --, Boy, two men and a horse --, Hauling hay the hard way --, Senseless mutilation, or operation for survival --, Lonely cowgirl --, Giving a word of thanks --, Horse trader's Christmas --, See him before you buy --, Day before Christmas --, That new-fangled Christmas gift --, How can I help you son? --, Cowboy --, Pardners --, Horse shoer --, Cowboy's challenge --, Helpful cow dog --, Showin' horses --, Horse trader --, Grow up --, Lonely cowgirl --, Spontaneous love --, Hard times --, Cowboy's reshoeing --, Resist all --, Levis --, Breed that wouldn't die --, knot on the ground --, Don don't leave me behind --, My friends talk to me --, Rodeo queen --, Cowboy's lament.

Cowboy (Eyewitness books, 45,, 1993)
Full-color photos. Trace the history and lore of a favorite folk hero--from ancient Mongolian herdsmen to South American gauchos to good ol' American cowpokes. Photos of actual clothing worn by famous cowboys and outlaws are included.

The cowboys (The Old West, ,, 1973)
This volume from the Time Life The Old West series examines through text and many photographs and illustrations the life of the cowboy in the American West. Chapters include cattle barons, the range, roundup time, long trail, beef boom towns, and code of the West.

The little cowboy and the big cowboy (Modern Curriculum Press beginning to read, ,, 2009)
Full-color illustrations and an easy-to-understand narrative describe the adventures of a cowboy and his son as they ride horses, round up cattle, practice roping, cook over a campfire, and sleep outdoors.

The Creed legacy (Creed cowboys, ,, 2011)
Explore the healing power of love and putting down roots in this classic Montana Creeds novel from New York Times bestselling author Linda Lael Miller! Rough-and-tumble rodeo cowboy Brody Creed likes life on the move. Until a chance encounter with his long-estranged twin brother brings him “home” for the first time in years. Suddenly Brody is in Creed territory—at thirty-three, he’s a restless bad boy among family with deep ties to the land and each other. And a secret past haunts him as he tries to make plans for his future. Carolyn Simmons is looking for Mr. Right in Lonesome Bend and hoping for a family of her own. Then she falls for gorgeous Brody Creed, the opposite of everything she wants. Until lassoing his wild heart becomes everything both of them need.   Previously published.   Read the entire fan-favorite Montana Creeds series: Book 1: Montana Creeds: Logan Book 2: A Creed in Stone Creek Book 3: Creed’s Honor Book 4: The Creed Legacy Book 5: Montana Creeds: Dylan Book 6: Montana Creeds: Tyler Book 7: A Creed Country Christmas   Don't miss author Linda Lael Miller's next heartwarming holiday drama, Christmas in Painted Pony Creek, where a single mom and her daughter find their lives magically changed and filled with the love and kindness of a man who would do anything to protect them.

Monte Walsh (Houghton Mifflin, University of New Mexico Press, Dreamscape Media, Pocket Books, University of Nebraska Press, 1963)
Monte Walsh has never met a horse he couldn’t ride, and Chet Rollins has never met one he couldn’t rope. For a decade they are unbeatable and inseparable, working as trail hands throughout the West until finally settling with Cal Brennan’s Slash Y. Their rough cowboy ethics see them through every imaginable challenge: blizzards, rustlers, outlaws, and card games gone wrong. Partial to pretty women, gambling, and practical jokes, Monte is often on the receiving end of trouble, while Chet is always there to break him out of jail or serve as a decoy until Monte can get out of town in a hurry. As the West begins to change, however—the automobile replacing the horse, the herds breaking up—the two friends part ways. Chet marries and goes on to become a successful merchant, banker, and politician; but Monte, unable to imagine anything but the cowboy’s way of life, refuses to the end to leave the range.
A beginning , Monte , Two of a kind , Slash Y , In harmony , X Y Z , Antelope junction , Christmas Eve at the Slash Y , Trail herd , Payment in full , Dobe Chavez , Hattie , Harmonizing , Powder Kent , Hellfire , All in one place , Drifters , A middle-aged man , An ending.

The American cowboy in life and legend (National Geographic Society, 1972)
Description Not Provided

Sun and saddle leather: including Grass grown trails and New poems (R. G. Badger : Gorham Press, Chapman & Grimes, R.G. Badger, 1920)
Description Not Provided
Illustrations: Badger Clark , When my feet is in the stirrups and my hawse is on the bust , There's a time to be slow and a time to be quick , We have gathered fightin' pointers from the famous bronco steed , taut ropes sing like a banjo string and the latigoes creak and strain , I wait to hear him ridin' up behind , There's land where yet no ditchers dig nor cranks experiment; it's only lovely, free and big and isn't worth a cent , When the last free trail is a prim, fenced lane and our graves grow weeds through forgetful Mays, richer and statelier then you'll reign, mother of men whom the world will praise. And your sons will love you and sigh for you, labor and battle and die for you, but never the fondest will understand the way we have loved you, young, young land.

Cow country (Tumbleweed, ,, 1995)
Life on the Western cattle range of the 1920's is recreated in these illustrated cowboy yarns
Wild horse --, When in Rome --, Montey of the "Y" Bench --, Silver-mounted --, Last catch --, Two old timers --, Complete --, Breed of 'em.

Sun up: tales of the cow camps (Drifting cowboy, ,, 1932)
Description Not Provided
His spurs , On the dodge , Makings of a cow-horse , Young cowboy , Cattle rustlers , Midnight , First money , Bucking horses and bucking-horse riders , His waterloo , Jake Adams, sourdough , Home guard , Filling in the cracks , Last catch , Cupid, the mustang , Silver-mounted , When in Rome.

Christmas in cowboy country (Cowboy Christmas, ,, 2014)
"A master storyteller. . .one of the world's most popular novelists." &;The Des Moines Register The greatest gift is love. . . Ski instructor Annie Bennett doesn't have time to miss the twinkling lights and holiday parties in Aspen and Vail. With her older brothers gone and winter just around the corner, her parents need help with their sprawling Colorado ranch. The most wonderful time of the year isn't always easy for a lot of the folks in their town, but Annie does her best--until the tall, dark, and rugged surveyor on their neighbor's land becomes a potent distraction. . . Wyoming born and bred, Marshall Stone is a practical man. But there's something about Annie that's as wild and sweet as the mountain wind. He doesn't want to tame her. Just love her. Annie Bennett is all he wants for Christmas. And for always. But she's too wary to believe he means it. Until he takes her in his arms and explains without saying a single word. . .

I see by your outfit: historic cowboy gear of the Northern Plains ; illustrated with historic photographs (High Plains Press, 1996)
No Hollywood flim-flam or arty photographic re-creation here. Lindmier and Mount demonstrate through the use of historic photographs what actual working cowboys of the Northern Plains wore and what equipment they used from the 1870s until 1928. These cowboys may not look like the ones in the movies, but you can bet your boots they are the real thing. The authors researched chaps, spurs, boots, and even underwear. Chapters cover saddles and horse gear as well as wagons. Over 120 historic photos and illustrations.
Foreword / John P. Langellier , The Northern Plains cowboy , Cowboy clothing , Riding gear , Horse gear , Bedrolls, camp equipment, chuck wagons , The real cowboy , Endnotes , Glossary.

Wyoming true (Wyoming men, 10,, 2020)
An opposites-attract love may be in store for a gruff rancher and a small-town beauty in a brand-new Wyoming Men romance Jake McGuire has worked hard to earn his success, with holdings that include ranches and a private jet. The only threat to his comfortable existence is the last woman he should ever want. He knows Ida Merridan by reputation only, but the stories he’s heard are enough for him to keep her at arm’s length, until the day fate puts her in his path under circumstances only the most heartless cowboy could ignore. Now, realizing the truth Ida’s been keeping, he’s powerless to give her up. Twice married and independently wealthy, Ida did nothing to deserve her bad reputation—except choose the wrong husbands. Live and learn in a small town, but after everything life has handed her, she’s in no hurry to make any more mistakes or be anyone’s object of pity. Being rescued by Jake throws a wrench into her plans for a solitary existence when one sizzling kiss leads to another, but her past is catching up with her, and there’s only so much she can do when Jake is determined to prove there are still some heroes left in the West. Don't miss the latest in New York Times bestselling author Diana Palmer's Wyoming Men series, Wyoming Homecoming! Wyoming Men: Book 1: Wyoming Tough Book 2: Wyoming Fierce Book 3: Wyoming Bold Book 4: Wyoming Strong Book 5: Wyoming Rugged Book 6: Wyoming Brave Book 7: Wyoming Winter Book 8: Wyoming Legend Book 9: Wyoming Heart Book 10: Wyoming True Book 11: Wyoming Homecoming

One-eyed cowboy wild (Leisure Books, G.K. Hall, Walker and Co, 1994)
When Zeke Hill kills the brutish and belligerent Charlie Bickford in a hand-to-hand fight, Zeke and his brother, Gene, both hands at the Redboot Ranch, decide to make the death appear accidental.

Matagorda (Bantam book, ,, 1986)
Tap Duvarney lost his innocence in the War Between the States and then put his skills to the test as a soldier in the frontier army. Now, leaving behind a devoted fiancée, he is trying to make his fortune on the Texas coast, working a ranch as the partner of his old friend Tom Kittery—and finding himself in the middle of a feud between Kittery and the neighboring Munson family. Around Matagorda Island, most people are either backing the Munsons or remaining silent. But the danger from outside Kittery’s camp is nothing compared to the threat within, as Tap begins to suspect that Kittery’s woman, a Texas-born beauty who misses the glitz and glamour of city life, isn’t everything she appears to be. Tap is quickly discovering that he must go to war again. But will it be with the Munsons—or with his closest friend?

The humor of the American cowboy (A Signet book, ,, 2006)
To the cowboy, for whom the world was a circus of creation, nothing was beyond the scope of laughter. His fertile imagination could produce trail drives of dry-land terrapins, cowboy firing squads for fighting game roosters, and a breed of "honk-honk birds" that could outrun a horse. He used humor to express his fondness for the West, to exchange sarcasms with railroaders, to teach lessons to tenderfeet, and even—sometimes—to laugh at death. In The Humor of the American Cowboy, Stan Hoig presents an authentic collection of tall tales, anecdotes, yarns, jokes, and humorous incidents of the Old West that not only entertain but also focus attention on a sometimes overlooked phase of cowboy life.
Illustrations: He let that poor ol' hoss come home all by itself , This is the best darned liver regulator I know about , Only 5,600 days to market , He tied his hoss to a brush clump , Little rain never hurt anybody , Doggoned if they weren't there , It was like having a town dog yappin' at your heels , No respect for schedules , Judge was mostly interested in the jingle in the pockets of the accused , He proceeds to guzzle snake pizen and hell 'round town , She caught him waterin' the sugar , Pete decided he didn't care much for working on the railroad , Cookie wasn't noted for his smilin' disposition , Greener was his favorite play toy , Pretty girls were as rare as clean socks in the bunkhouse , So that's the sour-faced old hussy , He'd risk his month's wages on the turn of a card.

Deadwood Gulch (Sidewinders, 5,, 2012)
The Greatest Western Writer Of The 21st Century Famed for his Mountain Man and Eagles epics, William W. Johnstone, with J.A. Johnstone, now introduces two hard-riding, trouble-prone Texans-with a knack for keeping the west as wild as it ever was. . . When A Devil Comes Calling, Meet Him With A Gun. . . Two years after Wild Bill Hickok made his mark on Deadwood, Scratch Morton and Bo Creel make theirs. Their job is guarding gold shipments from the mining camps-shipments that keep getting hijacked by a gang called the Devils of Deadwood who plunge pitchforks into their victims' bodies. With Thanksgiving approaching, Scratch just wants to carve a turkey with a handsome widow woman at his side. Course, when the U.S. Army comes to the rescue, all hell breaks loose. The widow gets taken hostage. So do a bunch of soldiers. Now, Scratch and Bo are going after missing gold and a band of vicious killers in the heart of a winter storm. Some days, it just doesn't pay to get out of bed.

Steamboat, legendary bucking horse: his life & times, and the cowboys who tried to tame him (High Plains Press, 1992)
Description Not Provided

Always a cowboy (Carsons of Mustang Creek, 2,, 2016)
Drake Carson is the quintessential cowboy. In charge of the family ranch, he knows the realities of this life, its pleasures and heartbreaks. Lately, managing the wild stallions on his property is wearing him down. When an interfering so-called expert arrives and starts offering her opinion, Drake is wary, but he can't deny the longing-- and the challenge-- she stirs in him. Luce Hale is researching how wild horses interact with ranch animals-- and with ranchers. The Carson matriarch invites her to stay with the family, which guarantees frequent encounters with Drake, her ruggedly handsome and decidedly unwelcoming son. Luce and Drake are at odds from the very beginning, especially when it comes to the rogue stallion who's stealing the ranch mares. But when Drake believes Luce is in danger, that changes everything-- for both of them.